Do Institutional Quality and Terrorism Affect the Natural Resources Rents? - Abid, Mehdi; Sekrafi, Habib; Farhani, Ramzi; Gheraia, Zouheyr; Abdelli, Hanane (International Journal of Energy Economics and Policy, 2024)
Despite the significant development observed in African countries’ economies thanks to the exploitation of natural resources, this has had very little impact on the daily lives of the population. Africa is also characterized by an increase in violent extremism, that is, the political, ideological, social and economic forces that support and fuel terrorism. Thus, a better understanding of the relationship between the possession of natural resources, terrorist attacks and institutional quality is essential for policy makers. Indeed, although being endowed with natural resources constitutes one of the pillars of growth and development, it is also the main funding source for terrorist groups in African countries. Our study covers a sample of 47 African countries over a period from 1996 to 2017. The terrorism variable takes four measures: uncertain, domestic, transnational and total. The research is based on three estimators, namely Ordinary Least Squares (OLS), Random Effects (RE) and System GMM. The paper argues that any increase in terrorist attacks contributes to the reduction of natural resources rents. Also, a country’s poor institutional quality contributes to poor exploitation of natural resources rents. Given the complementarities detected between terrorism, natural resources rents and institutional quality, improving institutional quality and reducing terrorism would lead to a better exploitation of natural resources.